Effect of H. pylori infection on gastrin, ghrelin, motilin, and gastroesophageal reflux - Eren, Makbule; Çolak, Ömer; Işıksoy, Serap; Yavuz, Aslı (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To evaluate the occurrence of gastroesophageal reflux and possible mechanisms in Helicobacter pylori infection. Materials and Methods: Symptoms of H. pylori-infected children, their total gastroesophageal reflux episodes, acid exposure percentage, gastrin, ghrelin, and motilin levels were evaluated before and after H. pylori eradication. Results: Forty-two H. pylori-infected children were eligible for this study. Acid exposure % and total reflux episodes before and after H. pylori eradication were 10.2%±14.8% vs. 7.71%±5.0% and 94.7%±102.1% vs. 64.6%±55.0%, respectively (p=0.28, p=0.082). There was an insignificant change in the serum gastrin (93.4±153.8 pmol/L vs. 1.28±149.4 pmol/L, p=0.67), ghrelin (7.69±197.5 pg/mL vs. 8.36±299.5 pg/mL, p=0.274), and motilin (75.1±81.2 pg/mL vs. 97.2±80.5 pg/mL, p=0.206) levels after eradication. Gastrin and ghrelin levels were negatively correlated after H. pylori eradication (r=−0.38, p=0.031). There was no association between gastroesophageal reflux episodes and gastrin, ghrelin, and motilin levels (r=0.25 and p=0.11; r= 0.24 and p=0.13; r=-0.23 and p=0.14, respectively) Conclusion: H. pylori infection is neither protective nor harmful in the gastroesophageal reflux. Neither ghrelin nor motilin levels was associated with gastroesophageal reflux. None of gastrin, ghrelin, and motilin levels was affected by H. pylori infection. There is an inverse association between gastrin and ghrelin levels after H. pylori eradication.